Sequestration of free and chelated Ni(II) by structural Fe(II): Performance and mechanisms. (1st January 2022) - He, Hongping; Wang, Jiaxin; Fei, Xunchang; Wu, Deli
Abstract: Ni(II) and chelated Ni(II) in wastewater are of environmental concern. This study explores the sequestration potential of structural Fe(II) in solid phase (≡Fe(II)) on Ni(II) and EDTA-Ni(II) using freshly prepared ferrous hydroxyl complex (FHC) as the Fe(II)-bearing mineral. The 1 mM Ni(II) could be completely sequestrated in 20 min by 3 mM FHC, although the sequestrated Ni(II) was partially released after 20 min. It is calculated that up to 156 mg Ni(II)/g Fe(II) can be sequestrated by ≡Fe(II) under neutral pH and anaerobic condition. According to the characterizations of the solid products, the large surface area for Ni(II) adsorption and the high ≡Fe(II) reduction capacity for Ni(II) reduction are the main contributors to the Ni(II) sequestration. After the reaction, the FHC is transformed to stable Fe–Ni layered double hydroxides. The concomitant ions can be either promotional or inhibitory to the sequestration performance depending on the ion type. The combination of FHC and Fe(III) can effectively sequestrate EDTA-Ni(II), whereas FHC alone has a low efficiency. Fe(III) substitutes Ni(II) from the EDTA-Ni(II), benefiting the subsequent Ni(II) sequestration by ≡Fe(II). This study demonstrates that ≡Fe(II) suspension is an cost-effective option for remediating Ni(II)-containing wastewater.